2021
DOI: 10.1007/s41348-021-00454-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide strategies and resistance of Ramularia collo-cygni to demethylation and succinate dehydrogenase inhibitors in Austrian winter barley (Hordeum vulgare)

Abstract: Ramularia collo-cygni B. Sutton and J.M. Waller is a major disease in Austrian barley-growing regions. To date, fungicide application is the most effective method to manage the disease; however, fungicide resistance to demethylation and succinate dehydrogenase inhibitors has developed over the last few years. In the growing seasons 2016/2017 and 2017/2018, field trials were carried out to analyze the efficiency of fungicide strategies based on different fungicide classes. Disease development, growth parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As a result, DMIs are regarded as being ineffective against R. collo-cygni in these countries [ 48 ]. Intensive monitoring of barley fields by Syngenta demonstrated that DMI field efficacy against RLS decreased from nearly 100% in 2014 to around 30% in 2019 [ 49 ]. The reduction in the control of R. collo - cygni by DMIs has increased concerns for future management of RLS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, DMIs are regarded as being ineffective against R. collo-cygni in these countries [ 48 ]. Intensive monitoring of barley fields by Syngenta demonstrated that DMI field efficacy against RLS decreased from nearly 100% in 2014 to around 30% in 2019 [ 49 ]. The reduction in the control of R. collo - cygni by DMIs has increased concerns for future management of RLS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR was established in Syngenta Resistance Centre in Stein, Switzerland. PCR assays were done according to the method described by Assinger et al (2021).…”
Section: Field Monitoringmentioning
confidence: 99%